Factors of ecological state forming for urbanized environment - Запорожець, О.І.; Мовчан, Я.І.; Гроза, В.А.; Савченко, В.І.; Соловейкіна, А.К.; Карпенко, С.В.; Шевченко, Ю.С. (Proceedings of National Aviation University (archive), 2010)
Factors of ecological state for modern urbosystems and results of their impact on population and environment have been investigated.